(untitled) (Agricultural Engineering, 2018)
The paper presents the outcomes of the research on the impact of shearing depth and flexibility of cultivator tines with cultivator points on the value of vertical forces acting thereon. The object of the research consisted in “S” tines with the flexibility coefficient of 0.0061; 0.0711; 0.0953 and 0.1406 m∙kN−1. The investigations were carried out in field conditions in sandy clay soil with moisture of 11.2%. The forces were measured for the assumed shearing depths which were 5, 9 and 13 cm at the shearing speed of 3 m∙s−1. A stand for measurement of forces acting on soil shearing tools in the field conditions was used. It was found out that the increase of the shearing depth causes a linear increase of the vertical force, but the force gradient decreases with the growth of the tine flexibility. Moreover, it was found out that the increase of the tine flexibility at the beginning causes the increase and then the decrease of the vertical force regardless the shearing depth. The impact of flexibility on the vertical force value was described with the parabola equation. The tines flexibility, at which the highest value of vertical force may be expected, grows with the reduction of the shearing depth.